2018
DOI: 10.2174/1567202615666180731100224
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Reduces Neuronal Loss and Inhibits the NLRP3 Inflammasome Activation in an Epileptic Rat Model

Abstract: Background: Epilepsy is a chronic neurological disorder affecting an estimated 50 mil-lion people worldwide. Emerging evidences have accumulated over the past decades supporting the role of inflammation in the pathogenesis of epilepsy. Curcumin is a nature-derived active molecule demonstrating anti-inflammation efficacy. However, its effects on epilepsy and corresponding mech-anisms remain elusive.Objective: To investigate the effects of curcumin on epilepsy and its underlying mechanism.Method: Forty Spragu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 40 publications
3
39
0
Order By: Relevance
“…After inhibiting NLRP3, neuronal necrosis and apoptosis levels in the same area of the hippocampus were significantly improved. Some scholars have found that curcumin can reduce convulsions by inhibiting NLRP3 to reduce levels of excitatory glutamate in neurons (11). In this study, NLRP3 and IL-1β were found to be involved in the occurrence and development of refractory temporal lobe epilepsy.…”
Section: Figure 4 |mentioning
confidence: 56%
See 1 more Smart Citation
“…After inhibiting NLRP3, neuronal necrosis and apoptosis levels in the same area of the hippocampus were significantly improved. Some scholars have found that curcumin can reduce convulsions by inhibiting NLRP3 to reduce levels of excitatory glutamate in neurons (11). In this study, NLRP3 and IL-1β were found to be involved in the occurrence and development of refractory temporal lobe epilepsy.…”
Section: Figure 4 |mentioning
confidence: 56%
“…The NLRP3 inflammatory corpuscle is a protein complex in the body that promotes the release of inflammatory factors in response to infection or tissue injury. NLRP3 inflammatory corpuscles are known to be associated with many nervous system diseases, such as Alzheimer's disease (AD), neurodegenerative diseases, and depression (9)(10)(11). Under normal circumstances, inflammatory corpuscles exist in an inactive form in microglia and astrocytes (12).…”
Section: Introductionmentioning
confidence: 99%
“…The NLRP3 inflammasome is the best characterized inflammasome and has been shown to be critical in driving the inflammatory response to sterile tissue damage [8,15]. NLRP3/ASC/ Caspase1-driven inflammation is pathological in the development of multiple neurological diseases, including Alzheimer's disease [10], Parkinson's disease [9], stroke [52] and epilepsy [12][13][14]. The TLE rat model established by amygdala stimulation shows increased hippocampal levels of NLRP3, active Caspase1 and IL-1b compared with those of controls [12].…”
Section: Discussionmentioning
confidence: 99%
“…Activated Caspase1 catalyses the maturation of the proinflammatory cytokines interleukin-1b (IL-1b) and IL-18 [8]. The NLRP3/ASC/Caspase1 cascade has been studied in the pathophysiological course of many central nervous system (CNS) diseases, including Parkinson's disease [9], Alzheimer's disease [10], multiple sclerosis [11] and epilepsy [12][13][14]. For instance NLRP3 inflammasome components are upregulated in the hippocampus following SE induction, and inhibition of the NLRP3 inflammasome ameliorates disease outcomes in a rat model of acquired epilepsy [12].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past half-decade, CUR has gained attention as a key molecule in neurological disorders, being tested both for its effectiveness and safety. Numerous preclinical studies have suggested its use in treating disorders such as AD [40,41], Parkinson disease (PD) [42,43], multiple sclerosis (MS) [44,45], migraine [46,47], epilepsy [48,49], stroke [50,51], traumatic brain injury [52,53], and spinal cord injury [54]. Various studies indicate that the antioxidant, anti-inflammatory, anti-amyloidogenic, antidepressant, antidiabetic, and antiaging properties of CUR are responsible for the neuroprotective effects as in Figure 2 [55][56][57].…”
Section: Curcumin and Neurological Disordersmentioning
confidence: 99%